Exploitation Of Natural Substrates And Oil Cakes For Pectinase Production By A.Tamarii & A.Carbonarius - SABIKA AKBAR; DR.R.GYANA PRASUNA; B.THEJA; Y.M.S. CHAKRADHAR (International Journal of Pharma and Bio Sciences, 2012)
The present work was carried out with an aim to isolate an Exo-pectinase producing fungal strain, to optimize physical factors of the enzyme activity and to formulate a media for the cost effective production of the enzyme. Screening, isolation and identification of Aspergillus tamarii and Aspergillus carbonarius were done. Various process variables like pH, temperature and incubation time of the growth medium were optimized. Modified media using natural wastes as C and N sources were used in combination for quantitative estimation of the enzyme activity. Optimization of various physical variables like pH, temperature, incubation period and substrate concentration for enzyme activity were done. Out of the various <a title="Find more articles at http://www.scialert.net/asci/result.php?searchin=Keywords&cat=&ascicat=ALL&Submit=Search&keyword=carbon+source (carbon source)" href="http://www.scialert.net/asci/result.php?searchin=Keywords&cat=&ascicat=ALL&Submit=Search&keyword=carbon+source" target="_blank" rel="noopener">C and N combinations tested, citrus peel and groundnut oil cake(GOC) were found to be the best C and N source for A.tamarii, Groundnut hull and groundnut oil cake were proved to be the best C and N source with respect to A.carbonarius. Orange peel and groundnut peel, a major waste by-product of food industries could be effectively used as C-source and GOC, a major waste of oil industry `can be used as N-source thus, making the process cost effective.